Cochrane Review: Osmotic and stimulant laxatives for the management of childhood constipation (Review). Issue 1 (3rd January 2013) - Gordon, Morris; Naidoo, Khimara; Akobeng, Anthony K; Thomas, Adrian G
Abstract Background Constipation within childhood is an extremely common problem. Despite the widespread use of osmotic and stimulant laxatives by health professionals to manage constipation in children, there has been a long standing paucity of high quality evidence to support this practice. Objectives We set out to evaluate the efficacy and safety of osmotic and stimulant laxatives used to treat functional childhood constipation. Search methods The search (inception to May 7, 2012) was standardised and not limited by language and included electronic searching (MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Inflammatory Bowel Disease and Functional Bowel Disorders Group Specialized Trials Register), reference searching of all included studies, personal contacts and drug companies. Selection criteria Randomised controlled trials (RCTs) which compared osmotic or stimulant laxatives with either placebo or another intervention, with patients aged 0 to 18 years old were considered for inclusion. The primary outcome was frequency of defecation. Secondary endpoints included faecal incontinence, disimpaction, need for additional therapies and adverse events. Data collection and analysis Relevant papers were identified and the authors independently assessed the eligibility of trials. Methodological quality was assessed using the Cochrane risk of bias tool.The Cochrane RevMan software was used for analyses. Patients with final missing outcomes were assumed to have relapsed. For continuous outcomes we calculated a mean difference (MD) and 95% confidence interval (CI) using a fixed‐effect model. For dichotomous outcomes we calculated an odds ratio (OR) and 95% confidence intervals (95% CI) using a fixed‐effect model. The chi square and I2 statistics were used to assess statistical heterogeneity. A random‐effects model was used in situations of unexplained heterogeneity Main results Eighteen RCTs (1643 patients) were included in the review. Nine studies were judged to be at high risk of bias due to lack of blinding, incomplete outcome data and selective reporting. Meta‐analysis of two studies (101 patients) comparing polyethylene glycol (PEG) with placebo showed a significantly increased number of stools per week with PEG (MD 2.61 stools per week, 95% CI 1.15 to 4.08). Common adverse events in the placebo‐controlled studies included flatulence, abdominal pain, nausea, diarrhoea and headache. Meta‐analysis of 4 studies with 338 participants comparing PEG with lactulose showed significantly greater stools per week with PEG (MD 0.95 stools per week, 95% CI 0.46 to 1.44), although follow up was short. Patients who received PEG were significantly less likely to require additional laxative therapies. Eighteen per cent of PEG patients required additional therapies compared to 30% of lactulose patients (OR 0.49, 95% CI 0.27 to 0.89). No serious adverse events were reported with either agent. Common adverse events in these studies included diarrhoea, abdominal pain, nausea, vomiting and pruritis ani. Meta‐analysis of 3 studies with 211 participants comparing PEG with milk of magnesia showed that the stools/wk was significantly greater with PEG (MD 0.69 stools per week, 95% CI 0.48 to 0.89). However, the magnitude of this difference is quite small and may not be clinically significant. One child was noted to be allergic to PEG, but there were no other serious adverse events reported. Meta‐analysis of 2 studies with 287 patients comparing liquid paraffin (mineral oil) with lactulose revealed a relatively large statistically significant difference in the number of stools per week favouring paraffin (MD 4.94 stools per week, 95% CI 4.28 to 5.61). No serious adverse events were reported. Adverse events included abdominal pain, distention and watery stools. No statistically significant differences in the number of stools per week were found between PEG and enemas (1 study, 90 patients, MD 1.00, 95% CI ‐1.58 to 3.58), dietary fibre mix and lactulose (1 study, 125 patients, P = 0.481), senna and lactulose (1 study, 21 patients, P > 0.05), lactitol and lactulose (1 study, 51 patients, MD ‐0.80, 95% CI ‐2.63 to 1.03), and PEG and liquid paraffin (1 study, 158 patients, MD 0.70, 95% CI ‐0.38 to 1.78). Authors' conclusions The pooled analyses suggest that PEG preparations may be superior to placebo, lactulose and milk of magnesia for childhood constipation. GRADE analyses indicated that the overall quality of the evidence for the primary outcome (number of stools per week) was low or very low due to sparse data, inconsistency (heterogeneity), and high risk of bias in the studies in the pooled analyses. Thus, the results of the pooled analyses should be interpreted with caution because of quality and methodological concerns, as well as clinical heterogeneity, and short follow up. However, PEG appears safe and well tolerated. There is also evidence suggesting the efficacy of liquid paraffin (mineral oil), which was also well tolerated.There is no evidence to demonstrate the superiority of lactulose when compared to the other agents studied, although there is a lack of placebo controlled studies. Further research is needed to investigate the long term use of PEG for childhood constipation, as well as the role of liquid paraffin. Plain Language Summary Laxatives for the management of childhood constipation Constipation within childhood is an extremely common problem. Despite the widespread use of laxatives by health professionals to manage constipation in children, there has been a long standing lack of evidence to support this practice.This review included eighteen studies with a total of 1643 patients that compared nine different agents to either placebo (inactive medications) or each other. The results of this review suggest that polyethylene glycol preparations may increase the frequency of bowel motions in constipated children. Polyethylene glycol was generally safe, with lower rates of minor side effects compared to other agents. Common side effects included flatulence, abdominal pain, nausea, diarrhoea and headache. There was also some evidence that liquid paraffin (mineral oil) increased the frequency of bowel motions in constipated children and was also safe. Common side effects with liquid paraffin included abdominal pain, distention and watery stools. There was no evidence to suggest that lactulose is superior to the other agents studied, although there were no trials comparing it to placebo. The results of the review should be interpreted with caution due to methodological quality and statistical issues in the included studies. In addition, these studies were relatively short in duration and so it is difficult to assess the long term effectiveness of these agents for the treatment of childhood constipation. Long term effectiveness is important, given the often chronic nature of this problem in children.